AN ANATOMY OF CORRUPTION. Issue 2 (9th May 2019) - Schmidtz, David
Abstract : Which social arrangements have a history of fostering progress and prosperity? One quick answer, falsely attributed to Adam Smith, holds that we are guided as if by an invisible hand to do what builds the wealth of nations. A more sober answer, closer to what Smith said and believed, is that if the right framework of rules—plus decent officiating—steers us away from buying and selling monopoly privilege and steers us toward being valuable to the people around us, we indeed will be part of the engine that drives human progress and the wealth of nations.